PENGARUH TRANSPARANSI ANGGARAN TERHADAP PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI DESA CIPOTAKARI - Nur Siti Azma AD Samat; Andi Astinah Adnan; Ahmad Mustanir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of budget transparency implemented by the Cipotakari village government, analyze the level of community participation in the village development planning process, and examine the effect of bidget transparency on community participation in village development planning. This study employed a quantitative approach with an associative research design. The population consisted of community members who participated in the village development planning metting (Musrembang) in cipotakari village. The sampling technique used was purposive sampling, with a total sample of 46 respondents who met the predetermined research criteria. Data were collected through questionnaires, observation, and documentation. The collected data were analyzed using SPSS software, including validity testing, simple linear regression analysis, coefficient of determination and hypothesis testing.